Product juggernauts : how companies mobilize to generate a stream of market winners - Deschamps, Jean Philippe; Nayak, P. Ranganath (Boston, Massachusetts : Harvard Business Review Press, 1995)
We wrote this book out of deep conviction that the companies that will survive and thrive are those that manage simultaneously to create consistently superior value for many groups, including their customers, shareholders, and present and future employees.
Introduction -- Core competencies -- Making it work in your company
Keywords: INDUSTRIAL MANAGEMENT